2013
DOI: 10.1111/obr.12132
|View full text |Cite
|
Sign up to set email alerts
|

Gestational weight gain in relation to offspring obesity over the life course: a systematic review and bias‐adjusted meta‐analysis

Abstract: Gestational weight gain (GWG) is considered one of the risk factors for future obesity in the offspring. However, the direction and strength of this association at different periods of offspring life is relatively unknown. This study investigates whether excess or inadequate maternal GWG during pregnancy influences the risk of offspring obesity at different stages in life. A systematic review of published articles was undertaken after a comprehensive search of different databases, and extracted data were meta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
136
4
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(150 citation statements)
references
References 47 publications
9
136
4
1
Order By: Relevance
“…Three meta-analyses were performed on the association between GWG and childhood obesity. [1][2][3] However, the metaanalyses did not take postdelivery weight gain into account, which is shown to contribute to additional development of childhood BMI in our study.…”
Section: Comparison With Earlier Studies and Interpretationmentioning
confidence: 71%
See 1 more Smart Citation
“…Three meta-analyses were performed on the association between GWG and childhood obesity. [1][2][3] However, the metaanalyses did not take postdelivery weight gain into account, which is shown to contribute to additional development of childhood BMI in our study.…”
Section: Comparison With Earlier Studies and Interpretationmentioning
confidence: 71%
“…A mother's gestational weight gain (GWG) is a risk factor for the development of overweight in her child. [1][2][3] However, it is not clear to what extent this effect is due to genetics, 4 a programming effect of maternal GWG on the fetus, 5 or a result of maternal lifestyle that already points toward a shared "obesogenic" environment in the course of childhood. 6 Maternal postdelivery weight gain could well represent this shared "obesogenic" environment.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Although some evidence suggests that extreme undernutrition during pregnancy may be associated with higher obesity risk in offspring, the more common occurrence is overnutrition during pregnancy (Herring et al 2012). Recent systematic reviews found that excessive GWG was associated with an increased risk for offspring obesity compared to adequate GWG (Lau et al 2014;Mamun Mamun et al 2014;Nehring et al 2013), with an overall pooled odds ratio of 1.4 (Mamun et al 2014;Nehring et al 2013). For example, Perng et al (2014) found that every 5 kilograms of GWG was associated with greater adiposity (measured total fat and trunk fat) and higher leptin in children at ages 6-10 years, independent of maternal prepregnancy BMI.…”
Section: Gestational Weight Gain (Gwg)mentioning
confidence: 99%
“…This dysregulation in body composition suggests that an energy surplus in utero acts independent of parental genetics with respect to predisposition for excess weight. In fact, according to recent systematic reviews and meta-analyses, excessive GWG increases the risk of childhood overweight/obesity by 30-40% [9,10], thereby propagating the intergenerational cycle of obesity and the proliferation of chronic disease [5]. This may be due to a host of sociopolitical and physiological factors that promote maternal resource storage, decrements in PA, a loss of metabolic control, and a partitioning of excess energy reserves to the fetus [5,11].…”
mentioning
confidence: 99%